Elektrické indukční pece ve slévárnách - Bruštík, Josef (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Cílem této bakalářské práce je vytvoření odborné rešerše na téma Elektrické indukční pece ve slévárnách a seznámit se blíže s touto problematikou. Stručně bylo popsáno rozdělení pecí, způsoby tavení na jednotlivých typech pecí. Dále na základě zjištěných poznatků bylo provedeno zhodnocení ekonomických a technologických výhod těchto tavících zařízení a následné doporučení, pro další použití ve slévárnách.

The main aim of this Bachelor thesis is to create a technical summary on the topic of “The electric induction furnaces in foundries” and be more closely familiar with this issue. A division of furnaces and ways of melting by particular types of furnaces are briefly described. On the basis of gained knowledge, an evaluation of economic and technical advantages of these melting devices was performed and subsequently it is recommended for further usage in the foundries.
Electric induction furnaces in foundries
Keywords: Elektrická indukční pec; cívka; tavenina; tavba; vsázka; Electric induction furnace; coil; meltage; melting process; burden